A Magic Triangle

Geometry Level 3

In the four squares above points A A , B B and C C are joined to form A B C \triangle{ABC} . Find the area of A B C \triangle{ABC} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

As A D B C AD || BC , S A B C = S B C D = 2 S_{ABC}=S_{BCD}=2

S S means the area of

Rocco Dalto
Jan 21, 2020

Using the diagram above, the area of the trapezoid A A B C D = 1 2 ( 2 2 ) ( 2 a + 2 ) = A_{ABCD} = \dfrac{1}{2}(2\sqrt{2})(\sqrt{2}a + \sqrt{2}) =

2 a + 2 2a + 2 and the area A A D C = 1 2 ( 2 a ) ( 2 2 ) = 2 a A_{\triangle{ADC}} = \dfrac{1}{2}(\sqrt{2}a)(2\sqrt{2}) = 2a

A A B C = A A B C D A A D C = 2 a + 2 2 a = 2 \implies A_{\triangle{ABC}} = A_{ABCD} - A_{\triangle{ADC}} = 2a + 2 - 2a = \boxed{2} .

I did it this way : Let the position coordinates of A A be ( 0 , a ) (0,a) , of B B be ( a + 1 , 3 ) (a+1,3) and of C C be ( a + 2 , 2 ) (a+2,2) . Then the area of A B C \triangle {ABC} is 1 2 ( a + 1 ) ( 2 a ) + ( a + 2 ) ( a 3 ) + 0 ( 3 2 ) = 2 \dfrac{1}{2}|(a+1)(2-a)+(a+2)(a-3)+0(3-2)|=\boxed 2 . Unfortunately I saw the solution before posting my solution.

A Former Brilliant Member - 1 year, 4 months ago
Chew-Seong Cheong
Jan 24, 2020

Let the side length of the bottom left square be a a and A A be the origin of an x y xy -plane. Then the coordinates of the vertices of A B C \triangle ABC are A ( 0 , 0 ) A(0,0) , B ( 1 + a , 3 a ) B(1+a, 3-a) , and C ( 2 + a , 2 a ) C(2+a, 2-a) . By trapezium rule the area of A B C \triangle ABC :

[ A B C ] = ( y B + y A 2 ) ( x B x A ) + ( y C + y B 2 ) ( x C x B ) + ( y A + y C 2 ) ( x A x C ) = ( 3 a + 0 2 ) ( 1 + a 0 ) + ( 2 a + 3 a 2 ) ( 2 + a 1 a ) + ( 0 + 2 a 2 ) ( 0 2 a ) = 3 + 2 a a 2 2 + 5 2 a 2 4 a 2 2 = 2 \begin{aligned} [ABC] & = \left(\frac {y_B+y_A}2\right)(x_B-x_A) + \left(\frac {y_C+y_B}2\right)(x_C-x_B) + \left(\frac {y_A+y_C}2\right)(x_A-x_C) \\ & = \left(\frac {3-a+0}2\right)(1+a-0) + \left(\frac {2-a+3-a}2\right)(2+a-1-a) + \left(\frac {0+2-a}2\right)(0-2-a) \\ & = \frac {3+2a-a^2}2 + \frac {5-2a}2 - \frac {4-a^2}2 \\ & = \boxed 2 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...